THE INTERVENING EFFECTS OF STUDENT AND SCHOOL RELATED FACTORS ON THE ACADEMIC PERFORMANCE OF BACHELOR OF SCIENCE IN CRIMINOLOGY - GUADAMOR, MAITA (International Journal of Arts, Sciences and Education, 2021)
Abstract: The Bachelor of Science in Criminology of the College of Criminal Justice Education at Cagayan State University Piat Campus is known of its high percentage in all board examinations administered by the Professional Regulation Commission since its first board takers in 2012. Academic preparations of criminology students are commendable in terms of enrolment from the very start, interview conducted, orientations given in order to set the standards of the college. The expectations from students, the services that the school could offer in order to prepare students in their 4-year stay before they would be awarded their diploma, and how to overcome trials and hardships as they go through their studies. Students will have to undergo series of screenings, applying the selection and retention policies of the college as approved by the Board of Regents. This study attempted to ascertain the intervening factors affecting the academic performance of the Bachelor of Science in Criminology students of Cagayan State University, Piat Campus. This study made use of the descriptive research method employing the questionnaire patterned from a published study of Delelis, Mary Grace as main data-gathering instrument. This study was conducted at the Cagayan State University, Piat Campus, where the respondents were the Bachelor of Science in Criminology students. The 156 respondents of this study were selected through convenience sampling who are enrolled for the First Semester of SY 2021-2022. The data gathered were tabulated, analyzed and interpreted using the descriptive statistics like frequency counts, rank, percentage and weighted mean. It was revealed in this study that the factors used were the student-related and school-related factors. From the results spawned that the respondents strongly agree on the significant influence of study habits and the availability of instructional materials on the extent of their academic performance. In the light of the foregoing results of this study, it is strongly recommended that appropriate study habits towards education must be instilled among students and the college or the University as a whole should look into the availability and improvement of its instructional materials and other learning facilities that may help enhance students’ academic performance.